Hottest, coldest, highest, deepest - Jenkins, Steve, 1952-2021. (Boston : Houghton Mifflin, 1998)
Describes some of the remarkable places on earth, including the hottest, coldest, windiest, snowiest, highest, and deepest.
Includes bibliographical references.
Keywords: Geography -- Juvenile literature; Geography -- Miscellanea